O espaço ficcional em narrativas de Júlia Lopes de Almeida: A viúva Simões e a falência - Guimarães, Cinara Leite (2015)
This research is a study of the novels A viúva Simões and A falência, by the Brazilian writer Júlia Lopes de Almeida, focusing on the construction of the fictional space. From the perspective of topoanalysis, based on the works of Borges Filho (2007), Brandão (2013), Tuan (1980) and Lins (1976), our aim is to investigate the presence of different spaces, public and private ones, and their functions in the corpus under analysis. From the perspective of gender relations, we propose to investigate the relations between space and characters, from the perspective of gender relations, enfasizing the female characters. In order to do this, we will proceed to an analysis of the context of production of such novels, of the issues taken up by the author and of other structural elements of the novelistic narrative, whenever required for a better understanding of the corpus.